[Translated article] Temporary work disability following trapezial resection and suspension arthroplasty for thumb carpometacarpal osteoarthritis - B. Occhi Gómez; M. Galvan Ortiz de Urbina; A. López Ruiz de Salazar; A.J. Alonso Benavente; Á. Rodrigo Alonso (Revista Española de Cirugía Ortopédica y Traumatología, 2024)
Purpose: The aim of this study is to assess the time to return to work (TRW) in patients undergoing trapezial resection using the Mini TightRope® system at our centre and to investigate factors that might delay return to work following this surgery. Material and methods: A retrospective study was conducted on patients who underwent Trapezial resection and suspensionplasty using the Mini TightRope® system between 2015 and 2016, with a minimum one-year follow-up. Telephone interviews were conducted along with a review of medical records and radiology reports, as well as temporary work disability documents, collecting epidemiological and occupational data. Groups were compared based on age, gender, dominant hand, biomechanical occupational requirements of the patients, and whether they had experienced prior temporary work disability. Results: A total of 36 patients (29 women and 7 men) with an average age of 55.7 years were included. The median time to return to work was 126 days. Self-employed workers re-entered the workforce 72 days earlier on average; workers who had experienced prior temporary work disability had a greater total temporary work disability duration and took 91 days longer to return to work compared to those who had not. Conclusions: Patients employed by others and those who had experienced prior temporary work disability before the surgery had longer temporary work disability periods. In our study, no differences were observed based on gender, dominant hand, or biomechanical work demands of the intervened patients. Resumen: Introducción: El objetivo de este estudio es evaluar el tiempo de reincorporación al trabajo (TRW) en pacientes sometidos a resección trapecial utilizando el sistema Mini TightRope® en nuestro centro e investigar factores que podrían retrasar el reincorporación al trabajo después de esta cirugía. Material y métodos: Estudio retrospectivo de los pacientes a los que se realizó una trapecectomía y artroplastia de suspensión mediante el sistema Mini TightRope® entre los años 2015 y 2016, con un seguimiento mínimo de un año. Se realizó una entrevista telefónica y una revisión de la historia clínica y de la radiología, recogiendo datos epidemiológicos y laborales. Se compararon los grupos por edad, sexo, mano dominante y requerimientos profesionales biomecánicos de los pacientes, así como haber estado en incapacidad laboral temporal (ILT) previo a la cirugía. Resultados: Se incluyeron un total de 36 pacientes (29 mujeres y 7 varones) con una edad media de 55,7 años. La mediana para la vuelta al trabajo fue de 126 días. Los trabajadores autónomos se reincorporaron 72 días antes (p = 0,004); los trabajadores que estaban en ILT previa a la cirugía tuvieron una ILT total mayor, y tardaron en volver al trabajo 91 días más que aquellos que no lo estaban (p < 0,001). Conclusiones: Los pacientes que trabajan por cuenta ajena y aquellos que estuvieron en ILT previa a la cirugía presentaron tiempos de ILT mayores. En nuestro estudio no encontramos diferencias por sexo, mano dominante o grado biomecánico laboral de los pacientes intervenidos.